Vase life enhancement of Mokara red orchid with Jatropha curcas L., Psidium guajava L and Andrographis paniculata (Burm.f) wall. ex Nees leaf extracts - Rahman, Md. Muklesur (2014)
A study was conducted on the effect of leaf extracts from Jatropha curcas, Psidium guajava and Andrographis paniculata on longevity of cut Mokara Chark Kuan ʻRedʼ orchid flowers. A major problem in cut flowers is shortening of vase life due to blockage of xylem vessels by microorganisms or air bubbles (bacteria and their products), thus, reducing water uptake. Mature green leaves, below the youngest shoot of each J. curcas and P. guajava branches, were collected and used for this experiment. In case of A. paniculata, 6 to 8 weeks-old leaves and stems were collected. Bioactive antimicrobial phytochemical compounds were identified in leaf extracts by gas chromatography-mass spectrometry (GC-MS). Export-grade cut Mokara orchid flowers, with 75% opened florets, were purchased from a commercial grower. Each flower was treated with vase solutions containing a commercial flower preservative, 8-Hydroxyquinoline citrate (8-HQC), and three natural flower preservatives from leaf extracts of J. curcas, P. guajava or A. paniculata. The flower preservative treatments comprised i) Control (125 mg 8-HQC/L) and, ii) Single leaf extract (SLE), iii) Double combinations leaf extracts (DCLE) and iv) Triple combinations leaf extracts (TCLE) at 5, 10, 15 and 20 mg/L. Sucrose (2%) and citric acid (3%) were added to each vase solution. The experiments were conducted using a completely randomized design, with five replications. J. curcas leaf extract contained nine bioactive antimicrobial compounds identified by GC-MS. The five major antimicrobial compounds in the extract were 9-hexadecenoic acid; 10-octadecenoic acid, methyl ester; 9,12-octadecadienoicacid (Z,Z); 9,12-octadecadienoicacid, methyl ester; and n-hexadecoic acid. Sixty-six bioactive antimicrobial compounds were identified in the P. guajava leaf extract. The most active antimicrobial compounds contained in the leaf extract were squalene; phytol; bicyclo; and azulene. In the A. paniculata leaf extract, 29 antimicrobial compounds were identified. The three unique antimicrobial compounds were hexadecanoic acid, methyl ester; 9,12,15-octadecatrienoic acid, methyl ester (Z,Z,Z)-; and 9,12-octadecadienoicacid, methyl ester. These findings indicate that the leaf extracts of J. curcas, P. guajava and A. paniculata could be used in agricultural applications as a source for natural flower preservative or biocide against microbes in the vase solution of cut flowers. The SLE treatments did not extend cut flower vase life due to high floret drop and fading of petals. Lower pH was found in the 15 mg DCLE-Pg+Ap/L treated vase solutions. Moreover, flowers in both vase solutions retained better petal colour than other treated flowers. However, in this study the SLE treatments had shorter flower shelf life compared to 8-HQC. Therefore, 15 mg DCLE-Pg+Ap/L were used for the subsequent experiments to evaluate longer shelf life of cut flower. The SLE treatments were not used for further experiments due to the short vase life of flowers. The 15 mg DCLE-Pg+Ap/L treated vase solution had lower bacterial count compared to the 15 mg DCLE-Jc+Ap/L. The 15 mg DCLE-Pg+Ap/L was more effective in vase solution uptake compared to other treatments. In P. guajava leaves extracts showed antimicrobial activities, while A. paniculata showed both antifungal and antibacterial activities. Therefore, DCLE-Pg+Ap had the potential as a natural preservative solution to extend vase life of cut flowers to 3 days compared to 8-HQC by reducing microbial growth. The pre-treatment pulsing with 5 mg AgNP/L for 24 h, was placed in leaves extract of P. guajava and A. paniculata (AgNP5+DCLE-Pg+Ap) treated vase solution effectively controlled microbial xylem blockage. AgNP5+DCLE-Pg+Ap had the potential as a natural preservative in minimizing microbial populations, and extending vase life of cut flowers. The results indicated that flowers treated with vase solution containing AgNP5+DCLE-Pg+Ap had a higher rate of solution uptake compared to flowers treated with 8-HQC. The 8-HQC vase solution contained trace amount of bacterial suspension of 5 × 108 colony-forming units (CFU)/mL of gram positive and gram negative bacteria and fungi as well as in AgNP5+DCLE-Pg+Ap treatment vase solution. Flower stems in AgNP5+DCLE-Pg+Ap treated vase solution showed better petal colour, as indicated by the L*, C* and h° values compared to 8-HQC. Thus, leaf extracts of P. guajava and A. paniculata have the potential as a cut flower preservative to minimize microbial populations and extend 7 more days vase life of cut flowers compared to 8-HQC.